Prevention under the Affordable Care Act (ACA): Has the ACA Overpromised and under Delivered?; Comment on "Interrelation of Preventive Care Benefits and Shared Costs under the Affordable Care Act (ACA)" - Carol Molinari (Kerman University of Medical Sciences, 2014)
This policy brief discusses preventive care benefits and cost-sharing included in health insurance provisions of the Affordable Care Act (ACA) legislation and highlights some consequences to Americans and the country in terms of healthcare costs and value.